Performance of varieties under different fertility levels in summer sesame (Sesamum indicum L.): PERFORMANCE OF VARIETIES UNDER DIFFERENT FERTILITY LEVELS IN SUMMER SESAME - PARNIKA ARYA; NAMRATA JAIN; ANAND KUMAR VISHWAKARMA; SHIVANI PALIWAL (Journal of Oilseeds Research, 2026)
A field experiment on the performance of sesame varieties under different fertility levels during the summer season was conducted during 2023-24 at the Sesame and Niger Research Farm, College of Agriculture, Jawaharlal Nehru Krishi Vishwa Vidyalaya (JNKVV), Jabalpur, Madhya Pradesh. The main objective of the study was to evaluate the performance of different sesame varieties under varying fertility levels during the summer season. The soil of the experimental site was sandy loam in texture, classified as Vertisol, and neutral in reaction. The experiment was laid out in a split-plot design with three replications. The main-plot treatments consisted of three fertility levels: F1 (75% RDF), F2 (100% RDF), and F3 (125% RDF), while the subplot treatments comprised five sesame varieties: V1 (TKG-308), V2 (JTS-8), V3 (TKG-22), V4 (GT-10), and V5 (GT-11). Among the tested fertility levels, 125% RDF (F3) consistently exhibited superior growth and yield attributes across all parameters. This indicates that 125% RDF is the optimum fertility level for achieving maximum productivity in summer sesame cultivation. Among the varieties tested, TKG-308 emerged as the best-performing variety, followed by GT-10, JTS-8, and TKG-22. TKG-308 recorded the highest plant height, number of branches per plant, dry matter accumulation, number of capsules per plant, seed yield, haulm yield, and harvest index across fertility levels. In contrast, GT-11 recorded the lowest productivity, indicating a lower response to increased fertility levels and reduced suitability for profitable cultivation.